Carnal Rhetoric : Milton's Iconoclasm and the Poetics of Desire - Cable, Lana (Book collections on Project MUSE., 1995)
In recent years, New Historicists have situated the iconoclasm of Milton's poetry and prose within the context of political, cultural, and philosophical discourses that foreshadow early modernism. In Carnal Rhetoric, Lana Cable carries these investigations further by exploring the iconoclastic impulse in Milton's works through detailed analyses of his use of metaphor. Building on a provocative iconoclastic theory of metaphor, she breaks new ground in the area of affective stylistics, not only as it pertains to the writings of Milton but also to all expressive language. Cable tra.